Formula Optimization and Characterization of Soybeans and Pearl Millet (Penisetum glaucum) Tempeh Using Simplex Lattice Design Methods - Nurrizky, Hafiz Aulia; Wirawati, Chandra Utami; Surfiana, Surfiana; Nirmagustina, Dwi Eva (Indonesian Food Science and Technology Journal, 2025)
Abstract—Tempeh is a traditional Indonesian fermented food produced through the fermentation of soybeans with mold. Despite Indonesia's reliance on imported soybeans, the country possesses a wealth of locally available grains that have the potential to serve as alternative raw materials for tempeh production. These alternatives remain underutilized and insufficiently explored. The objectives of this research are (1) to optimize formulas using Indonesian indigenous grains (enjelai, sorghum, and pearl millet) as soybean tempeh substitutes, and (2) to characterize the chemical, microbiological, and antioxidant properties of tempeh. The primary response variable used to determine the optimal formulation is protein content, which must comply with the standards outlined in SNI 3144:2015. A Design of Experiments (DOE) was conducted using Mixture Design on Design-Expert 13 software with the Simplex Lattice Design (SLD) method. The optimal formula was selected based on a degree of desirability close to 1, and the model was validated by producing substituted tempeh products according to the resulting equation. The results showed that an 80:20 ratio of soybeans to pearl millet produces tempeh that meets SNI standards. The cubic model adequately explains the relationship between the experimental and predicted data, Y = 0.158375X1 + 0.033704X2 + 0.0000650X1X2 + 0.000016X1X2 (X1 - X2), where Y is tempeh protein content, X1 is soybean content, and X2 is pearl millet content. Pearl millet tempeh contained 15.94% protein, 12.8% fat, 2.47% fiber, 3.05 APM/g of coliform bacteria, and no detectable E. coli.  However, pearl millet tempeh exhibited low antioxidant properties, as shown by IC₅₀ values of 2,395.22 µg/mL and phenolic content of 0.43 mg GAE/g.